Further considerations about the ophthalmic features of the Möbius sequence, with data of 28 cases - Souza-Dias,Carlos Ramos de (2007)
PURPOSE: There is no uniformity in the literature about the core features required to make the diagnosis of Möbius sequence. Originally, the minimum requirements were the bilateral paralysis of the VI and the VII cranial nerves. The bilateral facial nerve paralysis or paresis, often asymmetric, is common to all patients but some facts show that the isolated VI nerve palsy in the Möbius sequence is not the rule. 1) When there is an esotropia in Möbius sequence, it is often too small to be caused by a bilateral isolated VI nerve palsy. There are many cases in which there is no esotropia in the primary position and even some cases, though rare, with exotropia. 2) In most cases of Möbius sequence, the esotropia can be eliminated with a mere recession of the medial rectus muscles. 3) In most patients with Möbius sequence there is, besides the lateral rectus palsy, a variable degree of adduction limitation, which defines a horizontal gaze palsy. The authors present some arguments to show that the isolated lateral rectus muscle palsy cannot be considered as a sine qua non factor for the diagnosis of Möbius sequence. METHODS: The binocular alignment in primary position and the incidence of abduction and adduction limitations among 28 of the authors' consecutive patients with Möbius sequence and in patients of 5 other randomly selected publications are presented for comments. RESULTS: The eyes' position in primary position among 135 of those 6 authors' patients (28 belonging to the authors of this study and 107 to the other 5) were recorded; 55 of them (40.74%) had orthotropia and 9 (6.66%) had exotropia. Among 80 patients of 4 authors (22 belonging to the authors of this study and 52 to the other 3), in whom the horizontal versions were analyzed, 79 (98.75%) had limitation of abduction and 53 (66.25%) had limitation of adduction. COMMENTS: The authors emphasize that the recent studies have shown that inside the VI nerve nucleus there are two types of cells: those which axons form the ipsolateral abducens nerve and those (interneurons) whose axons reach the medial longitudinal fasciculus and ascend for innervating the subnucleus of the contralateral III nerve subserving the contralateral medial rectus. Because of this arrangement, a lesion at the region of the VI nerve nucleus generally causes a paralysis of the ipsolateral lateral rectus and the contralateral medial rectus muscles, which characterizes the ipsolateral horizontal gaze palsy. CONCLUSION: The definition of the Möbius sequence is the paralysis of the facial nerve and the horizontal gaze palsy, instead of a VI nerve palsy, as seen in most published papers.